Antiphospholipid syndrome and cardiac tumors - León-Jiménez, Franco E. (2023)
We present the case of a 31-year-old female patient with a history of bilateral staghorn lithiasis, who started the disease one month before admission with thrombocytopenia and autoimmune hemolytic anemia. She was diagnosed with Evans Syndrome, initially she had negative autoimmunity markers, finally presented progressive dyspnea and 4 intracardiac masses were found in the right atrium and positive markers for antiphospholipid syndrome. Despite anticoagulation and preparation for cardiac surgery, she presented sudden death.